In iron metal slurry reactor for wastewater treatment - Bigg, T (Cranfield University, 2002)
The corrosion of iron is a very old and complex phenomenon. Its employment for the treatment of wastewater began in the earliest around ten years ago, with few earlier exceptions. Most researchers have considered its application to groundwater remediation, and its use a a permeable reactive barrier material is well established. The aim of this research is to measure parameters that govern zero-valent iron treatment of wastewater with the treatment of industrial influents prior to discharge to municipal sewage treatment works particularly in mind.